The fat-mass and obesity-associated gene rs9939609 T allele is prominent among the native Mexican population and is associated with risk for Type 2 diabetes and metabolic dysfunction-associated steatotic liver disease - Sepulveda-Villegas, Maricruz; Panduro, Arturo; Leal-Mercado, Leonardo; Cardenas-Benitez, Juan Pablo; Ojeda-Granados, Claudia; Roman, Sonia (Frontiers in Nutrition, 2025)
BackgroundThe fat mass and obesity-associated (FTO) rs9939609 T>A polymorphism is associated with excess body fat and metabolic disturbances, including Type 2 diabetes (T2D) and metabolic dysfunction-associated steatotic liver disease (MASLD). However, the genetic effect of the T and the A alleles on the development of these diseases may vary among populations.ObjectiveThis study aimed to determine the distribution of the FTO rs9939609 T>A polymorphism in West Mexican populations with variable genetic ancestry and analyze its effect on an admixed cohort’s anthropometric and metabolic profile.MethodsIn a cross-sectional study, 684 unrelated adults from West Mexico were included. Subjects were grouped as Amerindian (Wixárika and Nahuas) or admixed: Mestizo-Caucasians (Cuquío, San Miguel-Los Altos, and Villa Purificación) and Mestizo-Guadalajara (Mestizo-GDL). FTO genotyping was determined by an allelic discrimination assay. Assessment of anthropometrics, diet composition, and metabolic profile among 333 Mestizo-GDL subjects and their association with metabolic risk factors was conducted considering the dominant model (AA + AT vs. TT).ResultsThe Wixárika group had the highest frequencies of the T allele (94%) and TT genotype (89%) among Amerindians, followed by mestizos from GDL (74% and 56%, respectively). In contrast, Mestizo-Caucasians from Cuquío had the highest A allele frequency (32.4%). No significant effect of the FTO genotype on body mass index (BMI)/body fat was observed in the Mestizo-GDL population. However, the TT carriers exhibited higher waist-to-height ratios (0.52 ± 0.07 vs. 0.49 ± 0.08), insulin levels (10.8 ± 7.3 vs. 8.8 ± 5.2 μU/mL), triglycerides (141.8 ± 66.5 vs. 125.8 ± 65.3 mg/dL), and VLDL-c (29.1 ± 14.8 vs. 25.6 ± 14.2 mg/dL) than AA + AT carriers. The TT genotype was associated with higher odds of hypertriglyceridemia (HTG) (OR = 1.7, 95% CI = 1.07–2.73, p = 0.027), insulin resistance (IR) (OR = 1.79, 95% CI = 1.06–3.07, p = 0.031), and hyperglycemia (HGL) (OR = 2.77, 95% CI = 1.5–5.36, p = 0.002). Multivariable logistic regression confirmed that TT genotype carriers had greater odds of HGL (OR = 2.50, 95% CI = 1.2–5.15, p = 0.013).ConclusionThe FTO T allele was prominent among native Mexicans. In contrast, the A allele prevailed among the Mestizo with higher European ancestry. The TT genotype carriers had higher odds of IR, HTG, and HGL, highlighting the genetic predisposition to T2D and MASLD in populations exposed to obesogenic and hepatopathogenic environments.